Abnormalities in cognitive-related functional connectivity can be used to identify patients with schizophrenia and individuals in clinical high-risk - Yangpan Ou; Zhaobin Chen; Ying Wang; Huabing Li; Feng Liu; Ping Li; Dongsheng Lv; Yong Liu; Bing Lang; Jingping Zhao; Wenbin Guo (BMC Psychiatry)
Abstract Background Clinical high-risk (CHR) refers to prodromal phase before schizophrenia onset, characterized by attenuated psychotic symptoms and functional decline. They exhibit similar but milder cognitive impairments, brain abnormalities and eye movement change compared with first-episode schizophrenia (FSZ). These alterations may increase vulnerability to transitioning to the disease. This study explores cognitive-related functional connectivity (FC) and eye movement abnormalities to examine differences in the progression of schizophrenia. Methods Thirty drug-naive FSZ, 28 CHR, and 30 healthy controls (HCs) were recruited to undergo resting-state functional magnetic resonance imaging (rs-fMRI). Connectome-based predictive modeling (CPM) was employed to extract cognitive-related brain regions, which were then selected as seeds to form FC networks. Support vector machine (SVM) was used to distinguish FSZ from CHR. Smooth pursuit eye-tracking tasks were conducted to assess eye movement features. Results FSZ displayed decreased cognitive-related FC between right posterior cingulate cortex and right superior frontal gyrus compared with HCs and between right amygdala and left inferior parietal gyrus (IPG) compared with CHR. SVM analysis indicated a combination of BACS-SC and CFT-A scores, and FC between right amygdala and left IPG could serve as a potential biomarker for distinguishing FSZ from CHR with high sensitivity. FSZ also exhibited a wide range of eye movement abnormalities compared with HCs, which were associated with alterations in cognitive-related FC. Conclusions FSZ and CHR exhibited different patterns of cognitive-related FC and eye movement alteration. Our findings illustrate potential neuroimaging and cognitive markers for early identification of psychosis that could help in the intervention of schizophrenia in high-risk groups.